Evaluación del dispositivo Crop Booster en el cultivo de pimiento (Capsicum annum L). en condiciones de riego por microaspersión - Velásquez Intriago, María Eliana (2022)
The Crop Booster technology implemented in the irrigation system optimizes both the quantity and the quality of the yields, helping the plants to grow stronger, healthier, with less fertilizers and pesticides. Improving soil health and nutrient availability, increasing root density and balancing nutrient uptake and utilization by plants. Finally, the general objective of the research was to evaluate the effect of the Crop Booster microtransmitter in a microsprinkler irrigation system implemented in the pepper crop. This research was carried out in the experimental farm La María of the UTEQ. The Design of divided plots was obtained where these were divided as: plots with the Crop Booster technology and without the technology plus the varieties (Cubanelle, Marconi, California Wonder). The device was installed on one of the main pipes while the other pipe did not use the device. The study made it possible to identify that the technology plus the varieties had optimal developments both morphologically and in yield, where the evaluated variables highlighted in yield Kg/Ha were limited, an average of 91.71 kg/Ha was obtained in the treatment with application of the technology, while the control treatment gave an average of 46.58 kg/Ha, being the treatment that achieved the lowest yield. According to the results, it was possible to demonstrate that the use of new technologies applied in irrigation systems and in the agricultural field allow us to reduce the use of fertilizers and other chemicals, thus obtaining fruits organically and, in turn, the improvement and increase in your performance.